Development and validation of fall risk perception scale for patients with Parkinson’s disease - Yang, Xin; Yao, Meiqi; Guo, Zhiting; Shen, Xuhui; Jin, Jingfen (Frontiers in Psychology, 2024)
Background: Perception assessment plays an important role in fall risk awareness and fall prevention. Parkinson's disease patients with motor dysfunction are at high risk of falling.Currently, no instrument has been explicitly crafted to assess the risk perception of fall in PD patients. The purpose of this study was to develop and validate the risk perception scale for PD patients (FRPS-PD), providing healthcare professionals with a effective assessment tool to enhance proactive fall prevention initiatives.Based on the Proactive Health theory and Risk Perception Attitude (RPA) Framework, the questionnaire was developed through literature review, semi-structure interview, expert consultation and pilot testing. A total of 428 patients with PD from Grade A tertiary hospitals in Shanghai, Hangzhou and Anhui from January 2023 to July 2023 were recruited. The items and dimensions in the scale were explored and confirmed using item-analysis, content validity, exploratory factor analytical (EFA), confirmatory factor analytical (CFA), internal consistency and test-retest reliability analysis.Results: A total of 16-items, 2-dimensions structure were identified, including 12 items of risk perception and 4 items of self-efficacy dimension. The cumulative variance of EFA model was 73.669%, further CFA showed that acceptable model fit (c 2 /df=2.226, RMSEA=0.074, NF=0.928, TLI=0.951, CFI=0.959, GFI=0.887 and AGFI=0.848). The content validity index was 0.956. The reliability of the scale was 0.952 using Cronbach's α coefficient method. The test-retest reliability was 0.944.Conclusion：The FRPS-PD is a valid and reliable measurement for evaluating fall risk perception level for individuals with PD in mainland China.